Character Building - Nesia Mu’asyara; Muhammad Alif Putra Isdiantoro; Adjar Djati Gumono; Afif Nur Fadhlillah; Alvian Rosyada Al Hikami; Muhammad Gigih Prasaja (Universitas 45 Surabaya, 2024)
This journal discusses the concept of character building as a process of developing individual character which includes moral values, ethics and positive behavior. This research aims to explore the importance of character building in the context of education and everyday life. The method used is a literature review which includes theories and best practices in character development. The research results show that character building plays an important role in forming individuals who are qualified, have integrity and are able to contribute positively to society.